2021
DOI: 10.1038/s41433-021-01864-9
|View full text |Cite
|
Sign up to set email alerts
|

Can the long term using of pregabalin in fibromyalgia affect the choroid and retinal nerve fiber layer?

Abstract: BACKGROUND: In this study, the effects of long-term pregabalin use on the choroid and retinal nerve fiber layer were investigated in the fibromyalgia disease. METHODS: The patient group consisted of 41 fibromyalgia patients using pregabalin. The control group consisted of 41 newly diagnosed fibromyalgia patients who had not received any treatment yet. Choroidal and retinal nerve fiber layer thickness measurements were performed with Cirrus HD-OCT (Carl Zeiss Meditec Inc., Dublin, CA, USA) 30 minutes after pupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The calculation of SUCRA indicated that PGB 450 mg was the best performing option for R30%, and AMT 25 mg for R50%; PGB 150 mg was the worst perform-ing drug in both cases (61). It is also important to remember that PGB has a thinning effect on the retinal nerve fibre layer and should therefore not be used to treat FM patients with retinal nerve fibre layer damage, such as those with diabetic retinopathy or glaucoma (62). Finally, a meta-analysis has shown that vitamin D supplementation is more effective than placebo in reducing Fibromyalgia Impact Questionnaire scores (but not visual analogue scale scores) (63).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…The calculation of SUCRA indicated that PGB 450 mg was the best performing option for R30%, and AMT 25 mg for R50%; PGB 150 mg was the worst perform-ing drug in both cases (61). It is also important to remember that PGB has a thinning effect on the retinal nerve fibre layer and should therefore not be used to treat FM patients with retinal nerve fibre layer damage, such as those with diabetic retinopathy or glaucoma (62). Finally, a meta-analysis has shown that vitamin D supplementation is more effective than placebo in reducing Fibromyalgia Impact Questionnaire scores (but not visual analogue scale scores) (63).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%